Popular Scottish Song Traditions at Home (and Away) - Dougal, Josephine Kathleen (Routledge Tailor Francis, 2011)
This article addresses the way in which collective ideas of cultural identity in song are appropriated and customised at the local level. More specifically, it examines how the cultural construction of Scottishness in popular song was deployed and mediated in my Scottish/Australian family's song repertoire. The substance of this article draws from a recent Ph.D. study of my own migrant family's Scottish song traditions in Australia. It thus considers how song performance served as a vehicle for the formation of family and cultural meaning.